Polysulfated Trehalose as a Novel Anticoagulant Agent with Dual Mode of Action. (17th March 2015) - Rashid, Qudsia; Abid, Mohammad; Gupta, Neha; Tyagi, Tarun; Ashraf, Mohammad Z.; Jairajpuri, Mohamad Aman
Abstract : Physiological hemostatic balance is a coordinated outcome of counteracting coagulation and fibrinolytic systems. An imbalance of procoagulant and anticoagulant factors may result in life threatening thromboembolism. Presently, anticoagulant administration is the first line of therapy for the treatment of these conditions and several anticoagulants have been approved, including various forms of heparin. However, the polyanionic nature and multispecificity of heparin pose several complications. Generally, the polysulfated compounds with antithrombotic potential are thought to have feasible synthetic procedures with much less bleeding, thus having favourable safety profiles. Here we report the synthesis of a novel compound, trehalose octasulfate and the assessment of its anticoagulation potential. Molecular docking of trehalose and trehalose octasulfate with antithrombin showed a specificity switch in binding affinity on sulfation, where trehalose octasulfate interacts with critical residues of AT that are either directly involved in heparin binding or in the conformational rearrangement of AT on heparin binding. An in vitro analysis of trehalose octasulfate demonstrated prolonged clotting time. Lead compound when intravenously injected in occlusion induced thrombotic rats showed remarkable reduction in the size and weight of the clot at a low dose. Delay in coagulation time was observed by analysing blood plasma isolated from rats preinjected with trehalose octasulfate. A decrease in Adenosine 5′-Diphosphate (ADP) induced platelet aggregation indicated a probable dual anticoagulant and antiplatelet mechanism of action. To summarize, this study presents trehalose octasulfate as a novel, effective, dual acting antithrombotic agent.